The influence of environment, host and vector on the spread of dengue fever - Ardat, Ardat; Naing, Nyi Nyi; Basaruddin, Basaruddin; Arfah, Nadia Wan (Science Midwifery, 2024)
This research investigates the impact of host factors on the spread of Dengue Hemorrhagic Fever (DHF) in Indonesia through a survey study focused on the human population affected by the disease. By operationalizing key variables derived from theoretical frameworks, the study assessed observable factors that influence DHF transmission. The findings underscore the importance of host-related factors in understanding the dynamics of DHF, providing valuable insights for the development of effective public health strategies. The study aims to reduce the burden of DHF on communities, protect vulnerable populations, and decrease the incidence of severe health complications. Emphasizing the significance of health habits and environmental influences, the research advocates for targeted interventions to enhance community resilience against DHF. Ultimately, the study highlights the need for ongoing public awareness and education initiatives to combat this persistent health challenge and prevent future outbreaks in Indonesia.